2006
DOI: 10.1096/fj.06-6016fje
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ influx through CRAC channels activates cytosolic phospholipase A2, leukotriene C4secretion, and expression of c‐fos through ERK‐dependent and independent pathways in mast cells

Abstract: Cytosolic phospholipase A2 (cPLA2) is a Ca2+-dependent enzyme that mediates agonist-dependent arachidonic acid release in most cell types. Arachidonic acid can then be metabolized by the 5-lipoxygenase enzyme to generate the proinflammatory signal leukotriene C4 (LTC4). Here we report that Ca2+ entry through store-operated CRAC (Ca2+ release-activated Ca2+) channels activates the extracellular signal-regulated kinases (ERKs), members of the mitogen-activated protein kinase family, within minutes and this is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(121 citation statements)
references
References 63 publications
3
118
0
Order By: Relevance
“…We previously found that activation of store-operated CRAC channels in mast cells triggered expression of the c-fos gene (20). To see whether such excitation-transcription coupling was driven by a local or global Ca 2ϩ signal, we stimulated a population of RBL-1 cells (a mast cell line) with thapsigargin, a Ca 2ϩ ATPase inhibitor on the endoplasmic reticulum, which depletes the Ca 2ϩ stores and thereby opens CRAC channels (6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously found that activation of store-operated CRAC channels in mast cells triggered expression of the c-fos gene (20). To see whether such excitation-transcription coupling was driven by a local or global Ca 2ϩ signal, we stimulated a population of RBL-1 cells (a mast cell line) with thapsigargin, a Ca 2ϩ ATPase inhibitor on the endoplasmic reticulum, which depletes the Ca 2ϩ stores and thereby opens CRAC channels (6).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently established that Ca 2ϩ microdomains near CRAC channels activate the cytoplasmic enzymes Ca 2ϩ -dependent phospholipase A 2 and 5-lipoxygenase via recruitment of the MEK/ERK pathway (20). This results in the generation of the intracellular messenger arachidonic acid, which is rapidly metabolized by 5-lipoxygenase to the proinflammatory paracrine signal leukotriene C 4 (18,20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IP 3 binds to its receptor (IP 3 R) on the endoplasmic reticulum (also called the calcium store) causing the release of calcium from stores [64] . An empty store results in the activation of both store-operated calcium channels and Ca 2+ -dependent signaling pathways, including inflammatory reactions [65,66] and apoptosis [64] . Onouchi et al reported that a G to A substitution in the 5'-untranslated region of CASP3 (rs72689236) is associated with susceptibility to Kawasaki disease in Japanese and in Americans of European descent [34] .…”
Section: Genetic Polymorphisms Of the Itpkc Signaling Pathway In Patimentioning
confidence: 99%